Implementasi Algoritma Decision Tree Untuk Mengetahui Faktor Kredit Macet Dan Lancar Di Koperasi Serba Usaha Daruzzakah Rensing Lombok Timur - Mahpuz, Mahpuz; yahya, yahya; wasil, wasil (Fakultas Teknik Universitas Hamzanwadi, 2020)
Credit is the main product of savings and loan cooperatives in an effort to increase profitability. The greater the credit issued, the greater the profit earned by a cooperative, each cooperative will package credit products in such a way as to be able to attract the attention of each customer.Â However, cooperative suati can find problems in channeling credit, such as those in the Daruzzakah Multipurpose Cooperative located in Rensing Village, West Sakra Subdistrict, East Lombok Regency, however, the cooperative some can find problems in channeling credit, such as those in the Daruzzakah Multipurpose Cooperative which is located in Rensing Village, West Sakra District, East Lombok Regency, in determining the creditworthiness of credit they always use statistical data, but the data does not guarantee whether during credit or non-performing loans. The Decision Tree algorithm will provide several options to see what factors are bad or current loans, this is done to classify which loans are smooth and bad so that in the future it can be anticipated early.DOI : 10.29408/jit.v3i2.2299